Coupling effect analysis and control for grid‐connected multi‐microgrid clusters. Issue 5 (1st April 2020) - Akhavan, Ali; Mohammadi, Hamid Reza; Vasquez, Juan C.; Guerrero, Josep M.
Abstract : The parallel grid‐connected inverters are coupled due to grid impedance, which introduces multiple resonances and might lead to instability of the whole system. Hence, considering the coupling effect among inverters and achieving a solution for resonance damping is necessary for designing the control system. With increasing the influence of microgrids, the interconnection of microgrids is inevitable. Therefore, new challenges emerge with the interconnection of microgrids. It can be expected that the impedance of connection lines and grid impedance, play the most important role in the coupling of microgrids. Accordingly, the coupling effect among microgrids should be considered in control system design as well as considering the coupling effect among parallel inverters. Otherwise, the interconnection of microgrids might degrade the quality of grid injected current, while the injected current of each microgrid satisfies the standards when it is individually connected. In this study, the coupling effect between the two interconnected microgrids is investigated. Also, the control system design for inverters considering the coupling effect among parallel inverters inside a microgrid and coupling effect of other microgrid is clarified, elaborately. Several simulations and experimental results on a small‐scale laboratory prototype verify the validity of the theoretical analysis and the effectiveness of the proposed scheme.